Peran Ilmu-ilmu Sosial dan Humaniora bagi Liberasi dan Humanisasi Teknologi - J. Nasikun (Jurnal Ilmu Sosial dan Ilmu Politik, 2005)
The development of technology requires the right anticipation. This rests on three reasons in which social sciences and can reduce the negative impacts towards the cult of technology. First, the development of technology will always create social transformation. Second, both positive and negative impacts on person, society and environment may result from the development. Third, the understanding of the forward and backward linkages is required on the bases of the relationships between the development of technology and the development of social, political and economic systems. This article examines the roles of social sciences and cultural studies in the liberalization and humanization of technology.